1990
DOI: 10.1007/bf00272616
|View full text |Cite
|
Sign up to set email alerts
|

Tamm-Horsfall protein-mRNA synthesis is localized to the thick ascending limb of Henle's loop in rat kidney

Abstract: Tamm-Horsfall protein (THP) has been previously detected in cells of the thick ascending limb of Henle's loop (TAL) of different mammalian species using immunocytochemical methods. A nearly complete identity between THP and uromodulin, an immunosuppressive glycoprotein present in the urine of pregnant females, has been established recently. This paper describes the cellular location of THP mRNA by high-resolution in situ hybridization using a [35S]-labeled human uromodulin cRNA (antisense-) probe of a length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 19 publications
2
74
0
2
Order By: Relevance
“…An 8.5-fold reduction of UMOD in Ddah1 PT2/2 suggests that functional changes in MAMEs and NO synthesis within the proximal tubule are communicated downstream along the nephron to the thick ascending limb, where UMOD is exclusively expressed. 41 A link between NO activity and UMOD expression was confirmed in wild-type mice exposed to a nonselective NOS inhibitor (L-NAME), which resulted in reduced UMOD protein expression in kidney tissue and urine. Of note, NO exerts regulatory control over two transcription factors-nuclear factor of activated T cells 42 and Oct-1 43 -both of which have consensus-binding sites in the promoter region of UMOD.…”
Section: Discussionmentioning
confidence: 92%
“…An 8.5-fold reduction of UMOD in Ddah1 PT2/2 suggests that functional changes in MAMEs and NO synthesis within the proximal tubule are communicated downstream along the nephron to the thick ascending limb, where UMOD is exclusively expressed. 41 A link between NO activity and UMOD expression was confirmed in wild-type mice exposed to a nonselective NOS inhibitor (L-NAME), which resulted in reduced UMOD protein expression in kidney tissue and urine. Of note, NO exerts regulatory control over two transcription factors-nuclear factor of activated T cells 42 and Oct-1 43 -both of which have consensus-binding sites in the promoter region of UMOD.…”
Section: Discussionmentioning
confidence: 92%
“…18,19 Aviv et al 20,21 reviewed previously reported clinical studies that indicated that the thick ascending limb (TAL) had a pivotal role in the susceptibility of Blacks to HTN. A mechanism was proposed in which an increase in NKCC2 activity could lead to the expansion of the extracellular volume and thus be associated with HTN.…”
Section: Discussionmentioning
confidence: 99%
“…9 TGF should not be affected in the HSV1-tk model because injury is limited to the TAL and spares the macula densa 22 ; however, to demonstrate conclusively that TGF activation is a major contributory factor would require tubular microperfusion studies. The presence of luminal casts suggests that tubular backleak from obstruction also contributes to AKI.…”
Section: Discussionmentioning
confidence: 99%